Dynamical analysis, circuit implementation and deep belief network control of new six-dimensional hyperchaotic system. Issue 4 (December 2018) - Yi, Lingzhi; Xiao, Weihong; Yu, Wenxin; Wang, Binren
In this paper, a new six-dimensional hyperchaotic system is proposed and some basic dynamical properties including bifurcation diagrams, Lyapunov exponents and phase portraits are investigated. Furthermore, the electronic circuit of this novel hyperchaotic system is simulated on the Multisim platform, and the simulation results are agreed well with the numerical simulation of the same hyperchaotic system on the Matlab platform. Finally, a control method based on Deep Belief Network is proposed to track and control the proposed hyperchaotic system. In this method, the function of the hyperchaotic system is studied by Deep Belief Network and a high precision fitting function is obtained. Then a controller which is composed of the fitting function and the tracking reference signal is designed to achieve the tracking control of hyperchaotic systems. Simulation results verify the effectiveness and feasibility of this method.